Repositioning Indonesia â€“ Thoughts on the Indo-Pacific - Milner, Anthony (JAS (Journal of ASEAN Studies), 2019)
Before considering how best to reposition Indonesia in the world â€“ and I will be looking, in particular, at Indonesiaâ€™s current Indo-Pacific initiative -Â  we need to ask how the world itself has been repositioned. The terms of reference for this conference go straight to this second question. They immediately highlight the theme of globalization, noting how it has promoted â€œgrowing connectivity among statesâ€ and â€œrevolutionized human interactionâ€. How then has this region been reconfigured over the last decades? Until the mid-20th-century the entire Asian region was either under European colonial rule or strong Western imperial influence. That is how the region was structured â€“ with the great centres of power in London, Paris, The Hague and Washington. After the extraordinary conquests by Japan, which effectively ended the Western imperial project, Asia was quickly drawn into the Cold War. Countries lined up as Communist or Anti-Communist, and some tried to sustain a degree of neutrality or equi-distance. At the end of the Cold War, in the last decade or so of the 20th-century, as is often commented, there was a unipolar moment â€“ an America-dominated world with a sense of globalization not merely being economic, but also a globalization of ideas. One commentator wrote of the â€˜end of historyâ€™ â€“ the US had won, he said, with its liberal democratic ideology. Communism had been annihilated, and Western liberalism had the â€˜wind in its hairâ€™. This said, there were still objections. Dr Mahathir in Malaysia and a number of bright Foreign Ministry intellectuals in Singapore spoke of â€˜Asian valuesâ€™. They said you had to understand Asian values to explain the great economic transformation taking place in Asian countries â€“ and there was also a need to respect Asian values in the political arena, and not just insist that all societies must develop in the same way. The democracy, human rights, and other supposed responsibilities of government which Westerners have tended to advocate, it was argued, are not necessarily universal norms.Â Â